Eefeitos de posicionamentos em “tilt” e “recline” na distribuição da pressão no assento de pessoas com tetraplegia - Gradim, Luma Carolina Câmara (2017)
The development of pressure ulcers (PU) in people with spinal cord injury (SCI) is a relevant factor and directly affects the health. Several preventive methods in a wheelchair have been researched for pressure relief, health promotion and disease prevention, such as PU. Some methods such as seating positioning system, different cushions and variable positions as tilt and recline seating systems, are most commonly used to relieve the pressure, and have been studied and achieved significant results for people with SCI in wheelchair. This study aims, thus, to evaluate the pressure redistribution buttock interface / cushion in areas susceptible to UP (sacrum, ischia) for the positions of tilt and recline in the wheelchair, in people with tetraplegia by spinal cord injury. In order to proceed to the research, we analyzed five people of both sexes with tetraplegia by LM, between 18 and 60 years. Was used a characterization form, a wheelchair simulator, ROHO ®High Profile Quadtro Select ™ cushion, a pressure mapping system, adaptations to the simulator and a questionnaire of satisfaction with the use of tilt and recline systems. As results, the pressure relief in the buttocks was better in higher angles, such as 10 ° tilt with 120 ° of recline, 20 ° tilt with 120 ° of recline and 30° tilt with 120° recline. But, even the smaller angulation positions resulted in pressure relief. Therefore, our results indicate that a greater angle of tilt and recline is needed to improve pressure redistribution compared to smaller angles. A position of 30° tilt combined with 120° recline is effective in relieving pressure on the ischial tuberosities and the buttocks.